2013
DOI: 10.1007/s13187-013-0557-y
|View full text |Cite
|
Sign up to set email alerts
|

Journal Clubs: An Educational Approach to Advance Understanding Among Community Partners and Academic Researchers About CBPR and Cancer Health Disparities

Abstract: Background Journal clubs may enhance the knowledge and skills necessary to engage in community-based participatory research (CBPR) that will ultimately impact cancer health disparities. This article: (1) describes an innovative approach to adapting the traditional journal club format to meet community and academic participants’ needs, (2) presents evaluation data, and (3) explores whether responses differed between academic and community members. Methods Five journal clubs occurred between February 2011 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The initial concept of creating a journal club specifically focused on LGBTQ-identified and culturally responsive health literature was proposed by Ohio University Heritage College of Osteopathic Medicine (OUHCOM) students and operationalized by faculty and staff, who customized the structure and processes of the club after examining best practices and modifying available resources from other journal clubs. 15,[17][18][19]22 First-and second-year students on the main OUHCOM campus received recruitment emails and flyers, class Facebook announcements, and word of mouth notifications. Investigators held an information session in September 2018.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The initial concept of creating a journal club specifically focused on LGBTQ-identified and culturally responsive health literature was proposed by Ohio University Heritage College of Osteopathic Medicine (OUHCOM) students and operationalized by faculty and staff, who customized the structure and processes of the club after examining best practices and modifying available resources from other journal clubs. 15,[17][18][19]22 First-and second-year students on the main OUHCOM campus received recruitment emails and flyers, class Facebook announcements, and word of mouth notifications. Investigators held an information session in September 2018.…”
Section: Methodsmentioning
confidence: 99%
“… 15 , 16 Journal club participation can also make physicians and medical students feel more comfortable and confident in their ability to evaluate study design, research methods, and results of peer-reviewed articles published in scientific journals, and stay current on medical developments. 17 - 19 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If there is support by the faculty, for example in the field of biostatistics, this can contribute to a successful JC (Afifi, Davis, Khan, Publicover, & Gee, 2006). Vadaparampil et al (2014) identified a further learning objective for JCs we consider as outstandingly important, namely "to increase critical thinking". Critical thinking is a competence everyone should develop during an academic career.…”
Section: Scientific Competences and Formal Academic Qualificationmentioning
confidence: 99%
“…31 Th e CHA concept is rooted in research that incorporates the use of lay health advisors. 32,33 It refl ects similar roles identifi ed in community-engaged research, such as community partners, 34 patient navigators, 35 promotoras, [36][37][38] and outreach workers. 39 Lay health advisor models have also been successful, cost-eff ective, community-level strategies.…”
mentioning
confidence: 99%